A study of hydride precipitation in zirconium. (April 2021) - Khan, I.A.; Cocks, A.C.F.; Chattopadhyay, J.
Abstract: Zirconium-based alloys used in nuclear reactors are susceptible to hydrogen pickup. When the hydrogen concentration in the solid solution exceeds the threshold limit (terminal solubility), a solid-state phase transformation occurs in these alloys. The zirconium hydride phase so precipitated is brittle and may influence the integrity of in-core structural components by various mechanisms, such as hydride blistering, delayed hydride cracking (DHC) etc. Precipitation which usually occurs by nucleation, growth and coarsening is typically influenced by the coherent stresses as well as the external stress field. In this work, Eshelby-type analyses are carried out to understand the mechanics and energetics associated with precipitation of zirconium hydrides. In particular, the role of elastic mismatch between the matrix and inclusion and the external stress in controlling the morphology and orientation of a hydride precipitate is analyzed. Elastic calculations lead to several interesting findings and reveal that under the influence of an external stress, a hydride precipitate has a tendency to reorientate along a certain crystallographic plane of the zirconium matrix. Incorporation of hydride plasticity, in our proposed scheme, leads to hydride reorientation at realistic magnitudes of applied stress. The strong anisotropy in interfacial energy, however, causes a hydride precipitate to remain parallel to the basal plane. Potential applications of our proposed numerical scheme to other relevant fields are also discussed. Highlights: A numerical scheme, based on the Eshelby theory, is developed for analyzing an elastic/plastic inclusion in an elastic matrix. A rigorous analysis of the various factors influencing the morphology and orientation of a hydride precipitate is presented.. · New closed-form equations for the orientation of disc and needle shaped precipitates under an external stress are proposed.. The effects of stress bi-axiality and the direction of applied stress on the orientation of a hydride precipitate are reported.. The effect of anisotropy in the interfacial energy on orientation of a disc shaped hydride precipitate is analyzed.